NEXUS MODELING OF TRAINEES’ SATISFACTION IN A SCIENTIFIC WRITING CONTEXT: AN EMPIRICAL INVESTIGATION (Malaysian Journal of Learning and Instruction, 2025)
Purpose – Scientific writing is one primary way scientists disseminate their discoveries to the broader scientific community. International journals’ extensive scope and stringent peer review procedures have earned them the gold standard for academic publications. However, writing in reputable international journals and publishing them is no easy task. This prompted various online courses to assist researchers in overcoming writing obstacles and raising the caliber of their work to the point where it is acceptable for publication in esteemed publications. The study had two goals: (i) to investigate the correlations between perceived self-efficacy, enjoyment, motivation for courses, online course design, time management, Technology Acceptance Model (TAM), and satisfaction with E-courses, and (ii) to examine whether the motivation for courses and perceived self-efficacy moderate time management.Methodology – This study employed a quantitative approach and randomly selected 184 trainees from Indonesia who took online courses for scientific writing. The questionnaire to gather the quantitative data used a five-point Likert scale format. Descriptive statistics were obtained using IBM’s SPSS 25 statistical software. The statistical program Smart-PLS 3.0 was used to handle the data analysis, and it used structural equation modeling to assess the measurement model and test the hypotheses.Findings – The measuring methodology supported the study constructs' convergent and discriminant validity. Three factors directly impacted Indonesian trainees' perceptions of the ease of use of e-courses: perceived self-efficacy, enjoyment, and online course design. Furthermore, there was a negative and significant moderating effect on motivation and the relationship between time management and perceived enjoyment. However, the relationship between online course design and time management was positively moderated by perceived self-efficacy. It was found that 69.9% of the variance in online course satisfaction could be explained by exogenous factors, such as perceived self-efficacy, enjoyment, and online course design, influencing perceived ease of use.Significance – E-courses in scientific writing assist in improving writing and getting published in reputable journals. Apart from enhancing the academic quality of one’s writing, they helped in networking and gaining a reputation abroad. Besides, it encourages Indonesian researchers and the Indonesian Ministry of Education, Culture, Research, and Technology to develop a more evidence-based national development framework that serves as a basis for more effective policy development and decision-making. The impact of perceived self-efficacy on perceived usefulness was found to be negligible. On the other hand, perceived usefulness and simplicity were positively and directly impacted by both perceived enjoyment and online course design. The TAM was not significantly affected by course motivation, although time management was. The satisfaction of trainees was also positively and indirectly impacted by the following four external factors: perceived self-efficacy, perceived enjoyment, course motivation, and online course design.